Respuesta :

(x-3)(x+2)
x-3=0 x=3
x+2=0 x=-2

Answer:

C.{3, -2}

Step-by-step explanation:

Solving the quadratic equation by factorization:

[tex]x^{2} - x - 6 = 0[/tex]

we will find two factors that when multiplied together will give [tex]-6x^{2}[/tex] and when added together will give [tex]-x[/tex]

the factors are : [tex]-3x[/tex] and [tex]2x[/tex]

check :

[tex]-3x[/tex] x [tex]2x[/tex] = [tex]-6x^{2}[/tex]

[tex]-3x + 2x = -x[/tex]

we will substitute this values into the equation , that is

[tex]x^{2} - 3x + 2x - 6 = 0[/tex]

[tex](x^{2} -3x ) + (2x - 6 ) = 0[/tex]

factorizing , we have

[tex]x ( x - 3 ) + 2 ( x - 3 ) = 0[/tex]

factorizing [tex]x-3[/tex] out , we have

[tex]( x -3 ) ( x + 2 ) = 0[/tex]

either [tex]x - 3 = 0[/tex]  or [tex]x + 2 = 0[/tex]

Therefore :

[tex]x = 3[/tex] or [tex]-2[/tex]